Communication of Information about Genetic Risks: Putting Families at the Center. Issue 3 (16th July 2017) - Mendes, Álvaro; Metcalfe, Alison; Paneque, Milena; Sousa, Liliana; Clarke, Angus J.; Sequeiros, Jorge
Abstract : Genetic information is a family affair. With the expansion of genomic technologies, many new causal genes and variants have been established and the potential for molecular diagnoses increased, with implications not only for patients but also their relatives. The need for genetic counseling and intrafamilial circulation of information on genetic risks grew accordingly. Also, the amount and, particularly, the complexity of the information to convey multiplied. Sharing information about genetic risks with family members, however, has never been an easy matter and often becomes a source of personal and familial conflicts and distress. Ethical requisites generally prevent healthcare professionals from directly contacting their consultands' relatives (affected or still at risk), who often feel unsupported throughout that process. We discuss here the communication of genetic risks to family members. We first consider genomic testing as a basis for family‐centered health care, as opposed to a predominant focus on the individual. We reviewed the literature on sharing genetic risk information with family members, and the associated ethical issues for professionals. Some clinical cases are presented and discussed, and key issues for meeting the needs of individuals and families are addressed. We argue that genetic information is inextricably linked to the family and that communicating about genetic risks is a process grounded within the broader milieu of family relationships and functioning. We conclude for the need for a more family‐centered approach and interventions that can promote sensitive attitudes to the provision of genetic information to and within the family, as well as its inclusion in educational and training programmes for genetic healthcare professionals.